Evaluating Concurrent Election Systems and Their Impact on Democratic Quality in Indonesia - Nadya Syalum Ramadhani; Muhammad Ikhsan Wicaksana; Muhammad Zaky Andriano; Rudi Santoso (Rule of Law Studies Journal, 2026)
Background: The implementation of concurrent elections in Indonesia represents a major political reform aimed at improving electoral efficiency and strengthening democratic governance. Despite these intentions, its application has generated ongoing debates regarding whether the system truly enhances democratic quality or instead introduces new challenges, such as increased electoral complexity and voter burden. Aims: This study aims to evaluate the concurrent election system and analyze its impact on democratic quality in Indonesia. Methods: This research adopts a quantitative approach by utilizing secondary data obtained from official election reports and democratic indicators. The analysis focuses on key dimensions of democratic quality, including voter participation, electoral competitiveness, and institutional performance. The data were examined using both descriptive and inferential statistical techniques to identify patterns and relationships between the implementation of concurrent elections and democratic outcomes. Result: The findings indicate that the implementation of concurrent elections tends to increase voter participation and improve administrative efficiency. However, the complexity of the electoral system also affects voters’ understanding and may influence the clarity of political representation as well as institutional effectiveness. Conclusion: Overall, the concurrent election system in Indonesia produces mixed effects on democratic quality. Therefore, policy adjustments and institutional strengthening are necessary to ensure that the system contributes more effectively to democratic consolidation.